2017
DOI: 10.1590/2359-3997000000251
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma with synchronous thyroid metastases: case report and literature review

Abstract: SUMMARYThyroid metastases are rare in clinical practice. We describe the case of an 85-year-old woman who was referred to our department due to a multinodular goiter with compressive symptoms and subclinical hyperthyroidism. The patient was also undergoing evaluation for a polyp in her left nasal cavity, which was then diagnosed as a malignant melanoma of the nasal mucosa. A thoracoabdominal magnetic resonance imaging obtained for cancer staging revealed a > 50% tracheal obstruction caused by the goiter. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Some studies have shown a higher incidence in women, while others have reported the opposite results; our data support the former. 10 Additionally, our data showed that at the time of diagnosis, 42 (76.4%) patients had multiple organ metastases (lung, liver, bone, and brain), which was similar (35%-80%) to previous results. 11 It has been reported that STTs from renal and breast cancer are usually single metastatic foci, which are consistent with our data.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…Some studies have shown a higher incidence in women, while others have reported the opposite results; our data support the former. 10 Additionally, our data showed that at the time of diagnosis, 42 (76.4%) patients had multiple organ metastases (lung, liver, bone, and brain), which was similar (35%-80%) to previous results. 11 It has been reported that STTs from renal and breast cancer are usually single metastatic foci, which are consistent with our data.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…The prevalence of synchronous non-thyroidal cancers in patients on surgical therapy of papillary thyroid cancer is approximately 14 % (25). The third most frequently associated synchronous non-thyroidal cancers is melanoma (26). When comparing with patients without another malignancy, those with an non-thyroidal cancers were elderly (56.4 ± 15.5 years) and had been exposed to radiation (27).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing with patients without another malignancy, those with an non-thyroidal cancers were elderly (56.4 ± 15.5 years) and had been exposed to radiation (27). Studies have shown that pathohistological features of papillary thyroid cancers are similar in patients with non-thyroidal cancer compared with ones in patients without additional malignancy (26,27). Despite the fact that patients with an non-thyroidal cancers were detected at a more severe level of disease than those without, additional estimation of each TNM category have shown absence of statistical distinction in the primary tumor size, or the rate of nodal or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Renal, pulmonary, and gastrointestinal cancers are the most frequent primary sources, but metastasis of malignant melanoma to the thyroid has been described as well. [3][4][5][6][7][8][9] Even rarer is the presentation of tumorto-tumor metastasis of a distant malignancy to a synchronous thyroid neoplasm, being cited only in a handful of case reports and small case series. [10][11][12][13][14][15] To the best of our knowledge, there has been only one prior reported case of tumor-to-tumor metastasis of a cutaneous malignant melanoma to a synchronous thyroid malignancy, which was a non-Hurthle cell follicular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic spread of malignancy to the thyroid gland is uncommon 1‐4 . Renal, pulmonary, and gastrointestinal cancers are the most frequent primary sources, but metastasis of malignant melanoma to the thyroid has been described as well 3‐9 . Even rarer is the presentation of tumor‐to‐tumor metastasis of a distant malignancy to a synchronous thyroid neoplasm, being cited only in a handful of case reports and small case series 10‐15 …”
Section: Introductionmentioning
confidence: 99%